Car Rental System With Rule Based Technique - Chin, Hong Jie (2022)
This research investigates the development of car rental system with rule-based technique. This research consists of three objective which are to study the rule-based technique, design and develop the rule-based technique and evaluate the performance of rule-based technique. This research is containing 30 participants for the requirement collection and user acceptance testing. This research chooses the rule-based technique to assist the customer on providing the suitable car rental listing in the car rental system. The car rental system is developed as a web application where allows the user easily to access the car rental system through their browser. There are two different interfaces for the user, first is the customer interface which includes the rule-based technique to assist the customer on renting their ideal car while the second is the admin interface which allows the staff to manage the car, service and rental. This research shows the improvement on providing the car rental listing to fulfil the customer satisfaction. Conclusion, the rule-based technique assists the existing car rental system to provide the better services for the customer.